Education and poverty nexus in Libya: granger causality approach period (2000-2022) - Dr. Osama Dawo Omran Ibrahim,; Dr. Mustafa S Almajdob, (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2025)
Using yearly data from 2000 to 2022, the study examines the causal relationship between Libya's poverty rate and education spending. To examine the causal relationship between the variables, we employed the Granger causality test framework of the vector autoregressive (VAR) model. the results of testing Granger’s causality that runs EDX to POVR for Libya country is a causal relationship. It is also clear from the results that there is not a causal relationship from POVR to EDX.